Reversing sintering effect of Ni particles on γ-Mo2N via strong metal support interaction - Lili Lin (Nature Portfolio, 2021)
Reversing the thermal induced sintering phenomenon and forming high temperature stable fine dispersed metallic centers is one of the ever-lasting targets in heterogeneous catalysis. Here the authors report the dispersion of metallic Ni particles into under-coordinated two-dimensional Ni clusters over γ-Mo2N.